Synthesis and characterization of [(HPO3)6Mo21O60(H2O)4]8−: a new redox active heteropoly blue cluster with layered shape containing a phosphite template that self-assembles under controlled microwave irradiation. Issue 8 (4th February 2016) - Jin, Xiang-xiao; Yu, Wei-dong; Nie, Yan-Mei; Liu, Meng-Shu; Yan, Jun
Abstract : A redox active layered shape [(HPO3 )6 Mo21 O60 (H2 O)4 ] 8− with a phosphite template is synthesised by a microwave-assisted method and characterized. Abstract : The microwave-driven synthesis of a heteropoly blue cluster yields a redox active cluster, [(HPO3 )6 Mo21 O60 (H2 O)4 ] 8−, templated by six phosphite anions whereby two phosphites template a tri-lucunary Mo15 Dawson structure, and one templates a Mo6 ring with two of the three remaining phosphites acting as bridging ligands connecting the ring to the Mo15 .